VALIDITAS DAN KEPRAKTISAN SILAB-IPA: SISTEM INFORMASI LABORATORIUM BERBASIS GOOGLE APPS SCRIPT UNTUK EFISIENSI ADMINISTRATIF - Akbar, Khoironi Fanana; Asna Zunairoh (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The science laboratory administration at MTs Darul Amien, which is still managed manually, causes inefficiencies in equipment lending services, inventory accuracy, and report preparation. This study aims to develop a Science Laboratory Information System based on Google Apps Script to improve administrative efficiency using the Research and Development (R&D) method with the 3D model (Define, Design, Develop). Product validation involved 2 material experts and 2 media experts, while testing was conducted on 17 users (2 users in the small group test and 15 users in the large group test). The validation results showed feasibility scores of 93.06% from material experts and 91.32% from media experts, while user responses reached 95.14% in the small group and 88.94% in the large group. In conclusion, the developed Science Laboratory Information System (SILAB-IPA) has been proven valid, feasible, and effective to implement in supporting administrative efficiency and building a modern science laboratory management system at MTs Darul Amien